Gender and young consumer ethics: an examination in two Southeast Asian countries - Fandy Tjiptono (2018)
© 2017, © Emerald Publishing Limited. Purpose: This study aims to examine and compare ethical perceptions between genders on various potentially unethical consumer situations in Indonesia and Thailand. Design/methodology/approach: A survey was conducted by distributing self-administered questionnaires to a convenience sample of university students in two large cities in Indonesia and Thailand. There are 278 respondents in Indonesia 158 participants for Thailand. Most respondents aged between 18-24 years. Findings: Indonesian youths were found to believe that “passively benefiting”, “questionable action” and “downloading” are more unethical than Thai youths do. The relationship between gender and consumer ethics is not consistent in Indonesia and Thailand. Female youths in Indonesia tended to be more ethical in four out of seven dimensions of Consumer Ethics Scales than their counterparts, while no gender differences were found in Thailand. Practical implications: The results show the different consumer ethics between Indonesia and Thailand that may reflect cultural variations, where Indonesia is more multicultural than Thailand. The mixed findings of the gender differences may suggest that there are no intrinsic gender differences in consumer ethics. Further, the results also provide implications for educators and public policy makers in both countries to encourage more active roles played by universities in building ethical sensitivity among future leaders. Originality/value: This is one of the few studies examining the impact of gender on consumer ethical behavior in Southeast Asian countries, where various unethical behaviors (e.g. buying and using pirated products) are prevalent.